Relatório de Estágio Profissional "Viagem no tempo: A passagem de aluno a professor" - Ricardo Jorge Ferreira Fernandes (2017)
This internship report is an integral part of the process of evaluation of the Professional Internship, which is a Curricular Unit inserted in the 2nd year of the 2nd cycle of the Masters of Physical Education Teaching in Basic and Secondary Education of the Faculty of Sport of the University of Porto. The purpose of this document is to report on experiences during the professional internship held during the 2016/2017 school year at Cerco Secondary School, belonging to the Cerco School Group. The structure of the internship report is divided into 5 chapters: 1) Introduction: refers to the professional internship framework; 2) Personal Framework: refers to the personal course and initial expectations regarding the professional internship; 3) Professional Practice Framework: it encompasses the institutional framework, presenting the school, the internship nucleus and the classes where the internship took place; 4) Realization of Pedagogical Practice: related to performance areas 1, 2 and 3. Area 1 includes the processes of design, planning, realization and evaluation of the teaching process. Area 2 describes the school activities developed. Area 3 refers to the research study where the behavior of the students is analyzed in relation to the teaching models applied in the classes, in a class of the 12th year; 5) Conclusions and Future Perspectives: focus on the reflection of this professional internship year and the influence of this stage on my professional and personal evolution, and, finally, my expectations regarding the future.